Sirah of Prophet Muhammad ﷺ and Shaping Minds (Inducting Sirah as a Compulsory Subject in Education System) - Dr. Shair Ali Khan; Dr. Nazir Ahmad; Dr. Arif Siddiq (Al-Amīr Research Journal for Islamic Studies, 2025)
Prophet Muhammadﷺ, the last of the prophetic chain, is the only source of peace for humanity and the only one who brought peace and satisfaction to the world. The Jews were waiting for him among the Jews, but when they confirmed His arrival in Bani Ismaiel since then they turned as severe enemy to the Last Messenger of Allah. They tried their best to harm Him, to distort His message through various actions, including translation of the Quran into other languages. Hence, in 1142 the French Abbot Peter the Venerable started a translation project to distort the meaning of the Quran and religious texts. Under this project Robert of Ketton translated the Quran with the title: Lax Mahumet pseudoprophete in 1143. It was rhetorically the best but worst semantically as a huge distortion was intestinally made in it. The same spirt of enmity is still found in its worst shape which can, surely, effect the mind of Pakistani people specifically the young generation. To shape the minds of our public under the golden teachings of our Prophet Muhammad (peace be upon him) there should be a developed syllabus designed for comprehension level of students starting from early childhood till higher academic levels including induction of officers in all governing bodies. Whenever these purified minds shaped with prophetic light and teaching will occupy positions of power they will surely rule with the justice full of sincerity. The influential way to shape the minds filled with the love of the last Prophet Muhammad (peace be upon him) is to induct Sirah as Compulsory Subject in the following academic and administrative areas: At Academic Level: in National Curriculum from Class One to Ph.D. level At Administrative level: In All Administrative Posts such as CSS, PPSC, FPSC. At All Forces Level: Pakistan Army, Pakistan Navy, Pakistan Air Force. At Judicial Level: In the Judicial Exams for the selection of Government Judges for All Courts of Pakistan. At Political Level: For all Parliamentarians: National Assembly and Senate. The International Islamic University, Islamabad can take the initiative to prepare a good syllabus for all levels in collaboration with the Faculty of Arabic, and the Faculty of Usuluddin. Key words: Sirah, Academic, Administrative, Education, Induction, Mind Shaping